Analisis Pelaksanaan Supervisi Pembelajaran Kepala Madrasah Aliyah Negeri Jeneponto, Sulawesi Selatan - Mualimin Ahmad; Ismail Tolla; Ratmawati Ratmawati (Madrasah Tsanawiyah DDI Cilellang, 2020)
This research is intended to examine the implementation of the supervision of the headmaster of Madrasah Aliyah Negeri Jeneponto, which includes: processes, techniques, as well as supporting and inhibiting factors. The type of this research is qualitative and the informants are the head of the madrasah, the deputy head of the madrasah, and two subject teachers. Data were collected using interviews, observation, and documentation. The data analysis technique was carried out by using qualitative descriptive analysis. The results showed that 1) the process of implementing the supervision of the headmaster of Madrasah Aliyah Negeri Jeneponto through three stages, namely preparation, implementation, and meeting back and follow-up. 2) There are two techniques in implementing the supervision of the headmaster, namely individual supervision and group supervision. Individual supervision technique in the form of class visits, inter-class visits, class observations, and individual meetings. Whereas in the group technique, the headmaster uses a meeting between the supervisor (headmaster) and the teachers. 3) The supporting factor for the implementation of the supervision is the readiness of the teacher to receive guidance and assistance from the headmaster; fostering good relations between fellow teachers and madrasah principals; a conducive madrasah climate; completeness of facilities and infrastructure; availability of adequate teachers and staff both in quantity and quality. The inhibiting factor is the limited time due to the many activities/duties of the head of the madrasah both inside and outside the madrasah.